1999
DOI: 10.1007/s002210050872
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of self-turning in the dark: comparison between active and passive rotation

Abstract: The present work compares passive and active rotations in darkness with the aim of characterizing the contribution of efferent and proprioceptive information to the perception of angular displacement. The perception of angular displacements was measured in 12 naive subjects (Ss), who either stood on a rotating platform (passive mode, P) or actively turned about their vertical axis by stepping around "on the spot" on a stationary platform (active mode, A). Rotations consisted of short acceleration epochs follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
35
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 29 publications
9
35
1
Order By: Relevance
“…Yet human path integration performance exhibits systematic errors. Characteristic overestimation and underestimation of traveled distances and turning angles and thus a tendency to bias toward certain displacements have been reported for path integration tasks in real and virtual environments Jürgens et al, 1999;Riecke et al, 2002;Seemungal et al, 2007;Glasauer et al, 2009b). Furthermore, systematic errors differ between studies: while participants correctly reproduced a 10 m distance in one study (Klatzky et al, 1990), they underestimated the same distance by 2 m in another one (Schwartz, 1999).…”
Section: Introductionmentioning
confidence: 87%
“…Yet human path integration performance exhibits systematic errors. Characteristic overestimation and underestimation of traveled distances and turning angles and thus a tendency to bias toward certain displacements have been reported for path integration tasks in real and virtual environments Jürgens et al, 1999;Riecke et al, 2002;Seemungal et al, 2007;Glasauer et al, 2009b). Furthermore, systematic errors differ between studies: while participants correctly reproduced a 10 m distance in one study (Klatzky et al, 1990), they underestimated the same distance by 2 m in another one (Schwartz, 1999).…”
Section: Introductionmentioning
confidence: 87%
“…We know that sensory activity among different types of mechanoreceptors is integrated or 'fused' to generate the patterns of neural activity that correspond to 'proprioception'; this has been demonstrated for proprioceptive sensations related to the interphalangeal joints of humans (Gandevia et al 1983), but is also evident in proprioceptive tasks related to whole body movements (Jürgens et al 1999). Yet the mechanisms by which such integration may occur are unknown.…”
Section: Proprioceptors -Unresolved Issuesmentioning
confidence: 99%
“…'Proprioception' and 'kinaesthesia' has for technical and other reasons traditionally most often been investigated in a behavioural context where it is particularly unlikely that the central nervous mechanisms for motor control are engaged, i.e. in passive subjects (but see, for instance Cordo et al 1995;Jürgens et al 1999). It would be of great theoretical and clinical value to define differences in specific control requirements as well as useful sensory sources in different behavioural contexts, e.g.…”
Section: Proprioceptors -Unresolved Issuesmentioning
confidence: 99%
“…To date, much of the prior scientific investigation of these phenomena has been conducted in small-scale laboratory experiments (e.g., Israel et al, 1993;Jürgens et al, 1999;Telford et al, 1995) or by means of desktop computer simulations (e.g., Jacobs et al, 1997;Rossano & Moak, 1998;Stanton, Wilson, & Foreman, 2003;Tlauka & Wilson, 1994) and the HIVE is uniquely poised to deepen their findings. For example, Stanton et al (2003) used a desktop VE to examine the information humans use when taking shortcuts.…”
Section: Processing Large-scale Environmentsmentioning
confidence: 99%
“…None of these methods of simulating navigation provides users with realistic proprioceptive or vestibular information. Yet, a great deal of research has shown that this nonvisual, body-based information can be critical for fully maintaining awareness of one's orientation in the environment (Beritoff, 1965;Glasauer, Amorim, Viaud-Delmon, & Berthoz, 2002;Israel, Chapuis, Glasauer, Charade, & Berthoz, 1993;Jürgens, Boß, & Becker, 1999;Klatzky, Loomis, Beall, Chance, & Golledge, 1998;Potegal, 1982;Telford, Howard, & Ohmi, 1995;Yardley & Higgins, 1998). As a result, the realism and ecological validity of many desktop VEs and CAVEs fall short of one's experience with moving through large-scale environments in the real world.…”
mentioning
confidence: 99%